(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is mostly an agricultural economy. Approximately 50% of India’s labor force is occupied in agricultural practices that make a significant contribution to its economy. This article describes key economic trends in the agricultural sector & Indian economy. Agriculture is an essential part of the development of India. The Indian economy has seen significant growth over the last decades. Agriculture & associated practices have often been adapted to reach global requirements, and shipments of different food goods have seen an growing rise, leading to economic development. India has become among the highest growing & most developed nations in the world. Our nation has made strong strides in various sectors in the last few years, and this has led to its economic development. A number of potential large-scale & small-scale industries have been developed in recent times & have also proven to have a positive impact on the Indian economy.